A Decision Model for the Order Sequence and Delivery Date Problem in Companies Manufacturing According to the Order - Alperen Calapoğlu; Melike Şişeci Çeşmeli; İhsan Pençe; Özlem Çetinkaya Bozkurt (Acta Infologica)
The orders received in the companies that manufacture according to the order are produced in the order of incoming demand. However, orders that cannot be produced on time or planned to be produced at a later date than the customer’s demand cause customer loss. In this case, the company needs to decide which customer’s order should be produced first. However, this decision can turn into a rather complicated problem due to different criteria that need to be evaluated. In this study, an integrated decision model has been proposed for companies that make production on order, to establish a balance between the profitability of the company and the satisfaction of customers, and to choose among indivisible orders within a limited time based on the maximum benefit according to this established balance. The created model has been carried out on a company that produces to order. While determining how to choose between indivisible orders under a limited capacity, the ability of heuristic optimization to produce fast and reasonable solutions is utilized. In the established model, the production times and delivery dates of the orders are also determined. In the study, multi-criteria decision-making methods are used to establish a balance between the profitability of the company and customer satisfaction. While the criteria and importance levels are determined by the Analytical Hierarchy Process method, the customers are evaluated under the criteria with the TOPSIS method. Afterwards, a mathematical model has been established, and the selection process is carried out with a genetic algorithm.